Perspekif Hukum Intenasional Dalam Sengketa Laut Natuna: Kasus Indonesia Dan China - Salira Niti Sara; Sarassati Garnita; Tita Wulansari; Marshanda Indriani Putri (Jurnal Ilmiah Wahana Pendidikan, 2023)
This paper analyzes the perspective of international law of the Natuna Sea dispute between Indonesia and China. Through the analysis of significant international legal instruments, including UNCLOS 1982, this writing confirms the legal position of Indonesia maritime claims that are rich in natural resources. Although the international legal perspective supports Indonesia, complications in the application of international law in the context of this dispute are also investigated. The security, economic and political involvement of these dispute is observed, as well as peaceful efforts that can be taken by both countries and the international community.